Tunnelling Behavior: Exploring Corporate Governance and Ownership Structure - Damisa, Arti; Hardana, Ali; Replita, Replita (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract This study examines how ownership structure and corporate governance quality affect tunneling behavior in Indonesia, with a focus on the moderating role of the number of subsidiaries. Quantitative research techniques and secondary data from the Indonesia Stock Exchange, business websites, and pertinent periodicals were used in the study. From 2016 to 2019, 474 observations from listed companies on the IDX—excluding non-financial firms—made up the sample. STATA 14.2 software was used to perform statistical studies, such as Pearson Correlation, OLS Regression, and Moderated Regression. The findings show that tunneling behavior is positively impacted by managerial ownership, government ownership, and corporate governance quality, but negatively by domestic ownership. However, tunnelling behavior is not much impacted by foreign ownership. while domestic ownership has a negative impact. Foreign ownership, on the other hand, does not significantly affect tunnelling behaviour. Notably, the number of subsidiaries strengthens the relationship between corporate governance quality and tunnelling behaviour. Keywords: Corporate governance quality; ownership structure; tunnelling behaviour; subsidiaries.   Abstrak Penelitian ini menguji bagaimana struktur kepemilikan dan kualitas tata kelola perusahaan mempengaruhi perilaku tunneling di Indonesia, dengan fokus pada peran moderasi jumlah anak perusahaan. Teknik penelitian kuantitatif dan data sekunder dari Bursa Efek Indonesia, situs web bisnis, dan majalah terkait digunakan dalam penelitian ini. Dari tahun 2016 hingga 2019, 474 observasi dari perusahaan yang terdaftar di BEI - tidak termasuk perusahaan non-keuangan - menjadi sampel penelitian. Perangkat lunak STATA 14.2 digunakan untuk melakukan studi statistik, seperti Korelasi Pearson, Regresi OLS, dan Regresi Termoderasi. Temuan menunjukkan bahwa perilaku tunneling dipengaruhi secara positif oleh kepemilikan manajerial, kepemilikan pemerintah, dan kualitas tata kelola perusahaan, tetapi secara negatif oleh kepemilikan domestik. Namun, perilaku tunneling tidak banyak dipengaruhi oleh kepemilikan asing, sedangkan kepemilikan domestik memiliki dampak negatif. Kepemilikan asing, di sisi lain, tidak secara signifikan mempengaruhi perilaku tunnelling. Khususnya, jumlah anak perusahaan memperkuat hubungan antara kualitas tata kelola perusahaan dan perilaku tunnelling. Kata kunci: Kualitas tata kelola perusahaan; struktur kepemilikan; perilaku tunnelling; anak perusahaan.